Derivation of Third Order MHD Equations - Jirkovsky, L.; Bo-ot, l. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 13 No 2 (2001), 2012)
As a continuation and improvement on previous works, we derive a third order MHD equation through a projection and perturbation formalism that we will apply to various MHD flows. It is shown that the model can be linked to the theory where structure and geometry of the particle plays a role in explaining turbulence.
Keywords: projection techniques, turbulence, non-equilibrium phase transition